RANTAI TATA NIAGA KARET RAKYAT DI BENGKULU - Rudi Hartono (Universitas Sebelas Maret, 2008)
Rubber represent one of the important commodity that managed by most society in Bengkulu province. Main problem in this present time is lowering of farmer market price. Related to the problems, this study will study marketing of people rubber. Study in the Bengkulu province with descriptive basic method analysis based on secondary and primary data the collected from field survey. This study aims to study marketing of people rubber in Bengkulu